2015
DOI: 10.1186/s12894-015-0089-3
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal abnormalities and Y chromosome microdeletions in infertile men from Morocco

Abstract: Background: Male infertility is responsible for 50 % of infertile couples. Thirty percent of male infertility is due to cytogenetic and genetic abnormalities. In Arab and North African populations, several studies have shown the association of these chromosomal abnormalities with male infertility. Our objective is to evaluate the frequency of chromosomal abnormalities and Y chromosome microdeletions in infertile men from Morocco. Methods: A total of 573 Moroccan infertile men (444 azoospermic and 129 oligozoos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
2
3

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 45 publications
0
18
2
3
Order By: Relevance
“…Chromosomal abnormality is the most common genetic cause of infertility (Zhang et al, 2015b). Male carriers of chromosomal abnormalities have often been found to be azoospermic or oligozoospermic (Naasse et al, 2015;Zhang et al, 2015b). Although balanced chromosomal forms exert no phenotypic effect on the carriers, they show variable influence on sperm counts, which can range from normal counts to oligozoospermia or even result in a total absence of sperm in the ejaculate (Zhang et al, 2015c).…”
Section: Introductionmentioning
confidence: 99%
“…Chromosomal abnormality is the most common genetic cause of infertility (Zhang et al, 2015b). Male carriers of chromosomal abnormalities have often been found to be azoospermic or oligozoospermic (Naasse et al, 2015;Zhang et al, 2015b). Although balanced chromosomal forms exert no phenotypic effect on the carriers, they show variable influence on sperm counts, which can range from normal counts to oligozoospermia or even result in a total absence of sperm in the ejaculate (Zhang et al, 2015c).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of studies assert that AZFc micro-deletions are the most frequent, followed by micro-deletions in the AZFb and AZFa sub-regions . The frequency of the occurrence of micro-deletions can be very fluctuating due to the differences in many factors like Y chromosome background, the ethnicity of the selected patients, clinical criteria for patient selection, and methodological approachs (Naasse et al, 2015). The aim of the present study is to identify the types of microdeletions within the AZF region in azoospermic and oligospermic patients in Duhok province.…”
Section: Introductionmentioning
confidence: 99%
“…Results from the studies above collectively demonstrated that the prevalence rate of AZF microdeletions in infertile men with azoospermia ranged from 3% to 55% (Ambulkar et al., ). We found that the total prevalence rate of AZF microdeletions in NOA patients who underwent testicular biopsy was 15.6%, which is higher than in other regions of China and other countries (3.9%–13.1%) (Akin et al., ; Ambulkar et al., ; Ferlin et al., ; Li et al., ) and lower than in some other countries (18.8%–20%) (Naasse et al., ; Sheikhha et al., ). The probable reason why the results were different was that our cohort was from NOA patients who underwent testicular biopsy.…”
Section: Discussionmentioning
confidence: 76%